Crescimento e desenvolvimento da mandioca e do milho em cultivo solteiro e consorciado - Schons, Alfredo (2006)
Cassava (Manihot esculenta Grantz) is one of the most important foods for man and for animals, especially in poor and emergent countries. Maize (Zea mays L.) is the third cereal more produced worldwide. These two crops are often grown in small farms of Rio Grande do Sul. The objectives this study were to estimate the phyllochron and to identify a morphological indicator based on the accumulated number of leaves (NF) on the main stem for the beginning of starch accumulation (IAA) in de fibrous roots of cassava grown in several planting dates, and to quantify growth, development and yield of cassava and maize in different plant spacing in monocropping and intercropping, considering two sowing dates of maize. Two field experiments were carried out in Santa Maria, RS, Brazil during 2005/2006. One experimental was with cassava variety RS 13, with four planting dates (28/09/2005; 11/10/2005; 16/11/2005 and 27/12/2005) and planted in 12 l pots, buried in the soil and spaced 0.8 m. Daily degree days (STd, °C day) were calculated starting at emergency. IAA was determined on the plants when one root reached a diameter of 0.01 m. NF on the date of IAA and the main sterm final leaf number (NFF) up to the first sympodial braches were determined. The phyllochron varied from 20.3 to 29.5 °C day leaf-1 with larger values in the two later planting dates. The NFF varied among the planting dates, increasing as planting was delayed. The NF at IAA was similar for the four planting dates and occurred when NF = 20,9 (±1,0)leaves. The other experiment was carried using the cassava variety RS 13 that was planted on 27/09/2005 and the maize variety BRS Missões sown on two dates: when 50% of the cassava plants were emerged and when the cassava presented five visible leaves. Twelve treatments were used characterizing different plants spacing in the monocropping and intercropping. Several growth, development and yield parameters of both crops were analyzed. Thermal time (Tb=14°C for cassava and Tb=10°C for maize) of some developmental phases and the phyllochron were calculated. Growth and development were not affected by plant spacing in both monocropping and intercropping. The greatest land use efficiency was obtained with intercropping cassava and maize, with cassava planted in a double row spacing of 1.6 x 0.5 x 0.6 m and a single row of maize spaced 0.8 x 0.21 m or two rows of maize spaced 0.4 x 0.42 m between the double row of cassava and maize sowed at cassava emergence.